Mutation of CEP72 Gene May Predispose Patients to Hepatotoxicity. Issue 7 (October 2020) - Pham, Robin; Hoeft, Alice; Roberts, Carol; Hamby, Tyler; Maloy, Charles; Ray, Anish
Abstract : Drug toxicities during treatment of acute lymphoblastic leukemia play a pivotal role in influencing the outcome as certain toxicities may impair treatment compliance. Polymorphisms in CEP72 have been linked to increased incidence of vincristine-induced toxicities, namely peripheral neuropathy. We hypothesize that polymorphisms in the same gene may increase a patient's risk of developing hepatotoxicity when receiving potentially hepatotoxic agents during chemotherapy. This report describes hepatotoxicity that first developed during consolidation in a patient homozygous for the CEP72 risk alleles. Bilirubin levels normalized following dose reduction of 6-mercaptopurine. The patient continues to tolerate maintenance therapy at a reduced dose of 6-mercaptopurine.